2019
DOI: 10.1371/journal.pone.0223240
|View full text |Cite
|
Sign up to set email alerts
|

Tidal inlet seafloor changes induced by recently built hard structures

Abstract: Tidal inlets are extremely dynamic environments that are often strongly modified by anthropogenic intervention. In this study, we describe the rapid evolution of a highly human-impacted tidal inlet, studied through repeated high-resolution multibeam surveys and geomorphometric analysis. We document the rapid change induced by new hard coastal structures built to protect the historical city of Venice (Italy). A new breakwater erected between 2011 and 2013 induced the formation of large scour holes with the cons… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
13
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 89 publications
2
13
0
1
Order By: Relevance
“…Change detection statistics presented in Table 5 suggests a very high dynamic of sediment substrates located in the Chioggia inlet, which is in line with other results found in the literature concerning bathymetry changes in 2002-2013 [37], and in 2004-2014 in the neighboring Lido inlet, located in the north of the Venice Lagoon [15].…”
Section: Discussionsupporting
confidence: 89%
See 3 more Smart Citations
“…Change detection statistics presented in Table 5 suggests a very high dynamic of sediment substrates located in the Chioggia inlet, which is in line with other results found in the literature concerning bathymetry changes in 2002-2013 [37], and in 2004-2014 in the neighboring Lido inlet, located in the north of the Venice Lagoon [15].…”
Section: Discussionsupporting
confidence: 89%
“…Such hard anthropogenic structures located in the inlets could substantially affect the hydrodynamics, sediment transport, and the benthic habitat distribution of the lagoon [36]. In particular, it was shown that the recent construction of the hard structures had a direct impact on the seafloor [15,37]. Hence, there is a pressing need to understand the spatial and temporal response of the seafloor.…”
Section: Study Areamentioning
confidence: 99%
See 2 more Smart Citations
“…The bathymetric position index (BPI), representing the marine version of the Topographic Position Index (TPI) introduced by [58], has been applied to several sedimentary [59], geomorphological [60] and seafloor habitat mapping [61] studies. The BPI has been recently used for benthic habitat mapping studies [62][63][64][65][66].…”
Section: Bathymetric Position Index (Bpi)mentioning
confidence: 99%